RUANG PERTUNJUKAN SENI DI BLOK M - Gary Cantonna Tamin; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2020)
As time goes by, people, especially in urban areas, tend to have individualistic characteristics due to their busy daily routines. Where most of the time spent at work, home or shopping centers. Humans as social creatures who should socialize and interact with others to meet social needs. To meet social needs in the current modern era, it takes a social container that can accommodate the activities of the surrounding community. So that people can meet with each other, socialize and also interact through these social media platforms. South Jakarta, precisely in the Blok M area, was known as a place for the gathering of young people of its time. However, at this time Blok M has begun to be abandoned by the community because other regions have more adequate gathering places. Blok M is an area that has a lot of art communities, such as street buskers, Japanese communities, contemporary music and much more. According to Richard Florida, creative people have the desire to do creative things and also get together with other creative people. This has a continuity where The Third place according to Ray Oldenburg, is a place where people can gather and interact with one another to meet their social needs. Blok M is an area that has a lot of art communities, such as street buskers, Japanese communities, contemporary music and much more. Blok M Performing Arts Space is present as the third space or